Foundations of fuzzy control : a practical approach - Jantzen, Jan. (Chichester, West Sussex, United Kingdom : John Wiley & Sons, 2013)
"Foundations of Fuzzy Control 2nd Edition: A Practical Approach has been significantly revised and updated, with two new chapters on Gain Scheduling Control and Neurofuzzy Modelling. It focuses on the PID (Proportional, Integral, Derivative) type controller which is the most widely used in industry and systematically analyses several fuzzy PID control systems and adaptive control mechanisms. Foundations of Fuzzy Control 2nd Edition: A Practical Approach sets out practical worked-through problems, examples and case studies to illustrate each type of control system; and is accompanied by a website that hosts downloadable MATLAB programs and a web based course on Fuzzy Control which is taught by the author"--
"This textbook aims to explain the behaviour of fuzzy logic controllers"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Automatic control; Fuzzy systems; Fuzzy automata; TECHNOLOGY & ENGINEERING -- Mechanical; Automatic control; Fuzzy automata; Fuzzy systems; Electronic books; Electronic books